A thorough assessment of 10-MDP primers in modern dental adhesive systems - Ahmed A Abduljawad; Harraa SM Salih; Omar F Tawfiq (Journal of Baghdad College of Dentistry)
Background: Dental primers are pivotal in achieving durable and reliable bonding between dental adhesives and tooth structures. Among the various primers’ components, the functional monomer 10-methacryloyloxydecyl dihydrogen phosphate is gaining significant attention owing to its unique chemical properties and bond-enhancing capabilities. Aims: This paper comprehensively reviewed current knowledge on the functional monomer 10-methacryloyloxydecyl dihydrogen phosphate. We focus on its chemistry, interactions with tooth substrates, interactions with zirconium and other metals, adhesive’s longevity, clinical applications, and potential drawbacks. Sources: Our sources are the Internet, such as Google Scholar and PubMed. Study selection: Studies investigating the efficacy of 10-MDP primers were included. Conclusions: The emergence of 10-MDP primers has significantly advanced the field of dental adhesives by providing reliable bonding solutions to enamel and dentin. The chemical interaction between 10-MDP and tooth substrates demonstrates remarkable adhesive strength and longevity.